PELAFALAN SIGHOT TAKLIK TALAK DALAM PERNIKAHAN DITINJAU DARI MAQASHID AL-SYARIâ€™AH - Syamsu Madyan; Nanda Rizkiya Putra; Ach. Faisol (Jurnal Hikmatina, 2019)
Marriage is one of the thing for perfecting the religion and regenerating a better generation in other that islam encouraged a family with peacefull and affection inside. marriage has a high level in life to keep this level, human should have a sacred bond based on islamic shariah in indonesia, having a habitual of sighot taklik talak but in the law and the regulation og marriage is unclear, so that in islam there is a maqashidÂ  al-syariah to help people analyze law problem which has no sollution .the aims of this research is to know the implication of law in pronounc sighot taklik talak and based on the view of maqhasid al-syariah This research used bibliography research or literature research which includes secondary data by bibliography techniques the date analysis used qualitative method supported by deductive logical thinking and checked by triangulation. Based on the islamic law and the regulation of marriage in indonesia the pronunciation of sighot taklik talak still debatebable in the practical slof all husbands read since the couple lack of comprehension about the important of sighot taklik talak.Keywords: Marriage, Taklik talak, Mqhosid Al-syariah